2015
DOI: 10.1002/jmri.25047
|View full text |Cite
|
Sign up to set email alerts
|

Impaired regulation of portal venous flow in response to a meal challenge as quantified by 4D flow MRI

Abstract: Purpose-Portal and mesenteric hemodynamics is greatly altered in portal hypertension patients. This study utilizes four-dimensional flow MRI to visualize and quantify changes in abdominal hemodynamics in patients with portal hypertension undergoing meal challenge.Methods & Materials-Twelve portal hypertension patients and six healthy subjects participated in the study. Baseline MRI was acquired after 5 hours of fasting. Post-meal MRI was obtained 20 minutes after subjects ingested EnSurePlus®(574mL). Imaging w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…It allows time-resolved three-dimensional visualization and retrospective quantification of blood flow at any location in a three-dimensional volume (14). Feasibility of four-dimensional flow in morphologic and hemodynamic assessment of the hepatic and splanchnic vasculature in adults with cirrhosis and portal hypertension has been demonstrated (27) and has also been used recently to measure the hemodynamic response of the portal venous system to a meal (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…It allows time-resolved three-dimensional visualization and retrospective quantification of blood flow at any location in a three-dimensional volume (14). Feasibility of four-dimensional flow in morphologic and hemodynamic assessment of the hepatic and splanchnic vasculature in adults with cirrhosis and portal hypertension has been demonstrated (27) and has also been used recently to measure the hemodynamic response of the portal venous system to a meal (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have been carried out in animals, with little data from humans, and studies have generally relied on techniques with limited reliability and accuracy to estimate regional blood flow. Recently, a study in humans using novel 4D-flow MRI has been carried out (9). This showed that postprandial blood flow responses in the splanchnic territory in patients with liver cirrhosis were impaired, compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (10) validated the accuracy of radial 4D flow MRI in the abdominal vasculature in a porcine model. This technique can make visible the vascular tree including collaterals and possibly gastroesophageal varices, and quantify the flow in these vessels (11) and characterize alterations in collateral blood flow (12). Furthermore, it is known that portal hypertension increases the azygos flow, which can be measured at phase-contrast MRI (13).…”
Section: Utaroh Motosugi MD Phd • Alejandro Roldán-alzate Phd • Pementioning
confidence: 99%
“…Assessment of the intra-and interreader variability of flow measurements made at 4D flow MRI is important when evaluating the performance of quantitative markers. Fortunately, the intra-and interreader variability of the radial 4D flow MRI method describing this work was extensively evaluated and previously reported by multiple authors (12,14,33). Another limitation is that we used only 4D flow MRI-based MR angiography for a morphologic assessment of varices.…”
Section: Quantitative Analysis Of 4d Flow Mrimentioning
confidence: 99%